Diseño e Implementacion de una red de telefonia Ip, para la empresa coopseguros del Ecuador a nivel Nacional basada en una Plataforma de Software libre - Obando Gómez, Fabricio Javier (2015)
This project is to deploy an IP telephony network in Coopseguros company of Ecuador, because the company has expanded and has several branches nationwide, so it is desired that the exchanges are interconnected with each other. During the development of this project a comparison between brands of IP telephony is performed to determine which is best for the company, just as gathering information on the current situation of the company was conducted to see if there is adequate infrastructure for the installation of IP telephony. IP telephone exchanges in each of the agencies Coopseguros of Ecuador, and parameters are set so that these plants can make what you want, just as supporting evidence to prove its functionality was performed was installed...